2010
DOI: 10.4314/ajcem.v11i2.53916
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial infections and the challenges of control in developing countries.

Abstract: Nosocomial infection is a recognized public health problem worldwide with a prevalence rate of 3.0-20.7% and an incidence rate of 5-10%. It has become increasingly obvious that infections acquired in the hospital lead to increased morbidity and mortality which has added noticeably to economic burden. However, after about three decades of nosocomial infection surveillance and control worldwide , it still remains an important problem for hospitals today. Studies have shown that most hospitals in developing count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(89 citation statements)
references
References 24 publications
5
83
0
1
Order By: Relevance
“…However, S. aureus was the only gram positive organism identified in the samples. This observation corroborates with the findings from other work where S. aureus was reported as the predominant gram positive bacterial isolate in wound infections (Samuel et al, 2010;Magiorakos et al, 2012). The antibiogram of the isolates screened in this study showed that over 90% of the bacterial species showed high level of resistance to most of the tested antibiotics (cloxacillin, erythromycin, amoxycilin, augmentin and tetracycline).…”
Section: Discussionsupporting
confidence: 83%
“…However, S. aureus was the only gram positive organism identified in the samples. This observation corroborates with the findings from other work where S. aureus was reported as the predominant gram positive bacterial isolate in wound infections (Samuel et al, 2010;Magiorakos et al, 2012). The antibiogram of the isolates screened in this study showed that over 90% of the bacterial species showed high level of resistance to most of the tested antibiotics (cloxacillin, erythromycin, amoxycilin, augmentin and tetracycline).…”
Section: Discussionsupporting
confidence: 83%
“…1,4 Hospitals provide a favorable transmission pathway for the spread of HAI, owing partly to poor infection control practices among health workers on one hand, and overcrowding of patients in most clinical settings on the other. 1,4,5 We evaluated the impact of a sensitization workshop on knowledge and awareness of HAI among the nurses of a teaching hospital in India.…”
Section:  Nurses Have a Critical Role To Play In Preventionmentioning
confidence: 99%
“…1,2 Of every 100 hospitalized patients at any given time, 7 in developed countries, and 10 in developing countries will acquire at least one HAI. 3 The prevalence of HAI in developed countries varies between 5% and 15% 5 and it varies between 5.7% and 19.1% in low-and middleincome countries.…”
mentioning
confidence: 99%
“…Control of wound infections has been very challenging due to widespread bacterial resistance to antibiotics and due to an increasing incidence of infection caused by methicillin -resistant Staphylococus aureus (MRSA) and polymicrobic flora 6 . Studies have shown that most hospitals in developing countries especially Africa, have rudimentary and highly compromised infection control programmes due to lack of awareness of the problem, lack of personnel , poor water supply, erratic electricity supply, poor laboratory back up and funding 7 . These factors are rife in most rural health care centres in Nigeria, and underscore the need for this study.…”
Section: Introductionmentioning
confidence: 99%